Social Commerce and Impulsive Buying Behavior Among Digital Native Consumers in Indonesia - Yusuf Yusuf; Siska Ernawati Fatimah (Politeknik Siber Cerdika Internasional, 2026)
Background: The development of social media is now used not only for communication but also as a shopping platform that is increasingly interactive and live. This condition makes it easier for individuals to be tempted into spontaneous shopping behavior. Objective: This study aims to examine the effect of social commerce on impulsive buying behavior among digital native consumers in Indonesia. Methods: A quantitative survey approach was employed, involving 180 digital native respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using simple linear regression. Results: The findings show that social commerce has a positive and significant influence on impulsive buying behavior, with a regression coefficient of 0.563 and a significance value of 0.000 (p < 0.05). The R² value of 0.352 indicates that approximately 35.2% of impulsive buying behavior can be explained by social commerce. Thus, the more frequently and intensely individuals interact within social commerce environments, the more likely they are to engage in impulsive purchasing. Conclusion: These findings provide practical guidance for digital marketers in developing effective social commerce strategies and underscore the importance of consumer awareness in managing impulsive buying tendencies in the digital era.